2006
DOI: 10.1007/s10346-006-0044-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrometeorological thresholds for landslide initiation and forest operation shutdowns on the north coast of British Columbia

Abstract: Debris flows and debris avalanches are the most widespread and hazardous types of landslides on the British Columbia north coast. Triggered by heavy rain, they pose risks to forestry workers in sparsely developed regions. The scarcity of long-term quality rain gauges and the lack of weather radar information create significant challenge in predicting the timing of landslides, which could be used to warn and, when necessary, evacuate forestry personnel. Traditional methods to relate rainfall antecedents and rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 17 publications
1
32
0
1
Order By: Relevance
“…Some previous studies have used 1 week of antecedent rainfall for analyzing the antecedent soil moisture and found that it is an important factor for triggering landslides (Crosta 1998;Jakob 2006). Therefore, we also examined rainfall totals for 168 h (1 week) before the beginning of rainfall events that triggered mass movement events.…”
Section: Rainfall Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have used 1 week of antecedent rainfall for analyzing the antecedent soil moisture and found that it is an important factor for triggering landslides (Crosta 1998;Jakob 2006). Therefore, we also examined rainfall totals for 168 h (1 week) before the beginning of rainfall events that triggered mass movement events.…”
Section: Rainfall Datamentioning
confidence: 99%
“…This indicates that G2 is composed primarily of landslides, with release mechanisms directly related to hillslope hydrology. Soil moisture content is directly related to landslide occurrence (Terlien 1998;Wu and Chen 2009), and high antecedent rainfall elevates moisture content (Glade 1997;Crosta 1998;Crozier 1999;Glade et al 2000;Jakob 2006). Therefore, abundant antecedent rainfall combined with high-intensity rainfall can easily trigger landslides, especially around the time of peak rainfall.…”
Section: Rainfall Conditions and I-d Thresholdsmentioning
confidence: 99%
“…Many systems have been developed for densely populated mountainous areas throughout the world. Recent examples are available from Canada (Jakob et al 2006), Italy (Bacchini and Zannoni 2003), Taiwan (Chang 2003;Chen et al 2005;Kung et al 2008), China (Brand et al 1984;Zhang 1993), and Japan (Hirano 1997;Itakura et al 1997;Tanabashi 1998).…”
Section: Introductionmentioning
confidence: 99%
“…20 Different numbers of days have been considered and examined by researchers to find the most suitable correlation with landslide initiation (Aleotti, 2004;Polemio and Sdao, 1999;Zêzere et al, 2005). Of the issue, the researchers have proposed different numbers of days, however, only with local validity, which means that suggested rainfall thresholds are applicable to the respective study cases, and it also depends on the landside type (Jakob et al, 2006;Martelloni et al, 2012). Therefore, we referred to the domestic research results in that characteristics of local geology, soil and vegetation, as well as precipitation 25 patterns are different from the areas of other studies.…”
Section: Rainfall Threshold Triggering Landslidementioning
confidence: 99%
“…Despite the limitation on the accumulated landslide inventory data over the study region, the frequency of landslide occurrence was estimated by establishing a rainfall threshold. The selection of the rainfall threshold has been examined and proposed by various methodologies (Crozier, 2005;Guzzetti et al, 2007;Zêzere et 25 al., 2005;Frattini et al, 2009;Crosta and Frattini, 2003;Aleotti, 2004;Polemio and Sdao, 1999;Caine, 1980), and it has been shown that proposed rainfall thresholds are applicable to the respective study cases depending on the landside type with local validity (Jakob et al, 2006;Martelloni et al, 2012), so the criteria of cumulative precipitation and daily rainfall intensity for rainfall threshold setting were determined by referring to the local research results.…”
Section: Introduction 25mentioning
confidence: 99%